2020
DOI: 10.1021/acssuschemeng.0c02024
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Growth of Mung Bean Plants through Uptake and Light Conversion of NaYF4:Yb,Er@CDs Nanocomposites

Abstract: In recent years, the application of nanomaterials in promoting plant growth and augmenting photosynthesis has aroused great interest. Herein, carbon dots (CDs) are combined with NaYF4:Yb,Er to achieve an enhanced upconversion red emission. The effects of the obtained NaYF4:Yb,Er@CDs nanocomposites on the growth of mung bean plants are investigated. It is found that an appropriate concentration of the NaYF4:Yb,Er@CDs nanocomposites (0.5 mg/mL) can enhance the water absorption ability of hydroponic mung beans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 71 publications
0
43
0
Order By: Relevance
“…Carbon nanomaterials can work with up-conversion optical materials to promote nIR light conversion to enhance plant photosynthesis [101,102]. Doping CDs into the up-conversion material NaYF4: Yb, Er, CDs can shift the green emission of NaYF4: Yb, Er to red light [103]. Mung beans sprayed with NaYF4: Yb, Er@CD nanocomposite showed a significantly increased photosynthetic rate [103].…”
Section: Cnms As An Up-conversion Light Convertermentioning
confidence: 99%
“…Carbon nanomaterials can work with up-conversion optical materials to promote nIR light conversion to enhance plant photosynthesis [101,102]. Doping CDs into the up-conversion material NaYF4: Yb, Er, CDs can shift the green emission of NaYF4: Yb, Er to red light [103]. Mung beans sprayed with NaYF4: Yb, Er@CD nanocomposite showed a significantly increased photosynthetic rate [103].…”
Section: Cnms As An Up-conversion Light Convertermentioning
confidence: 99%
“…[58] In the study by Xu et al NaYF4:Yb,Er combined with CDs showed efficiently an increase in the length of root/stem as well as the weight of dry/wet of mung bean seedlings by using spraying these nanocomposites. [59] In another research by Aji et al [60] the beneficial influence of CDs exhibited in enhancement of plant growth of Ipomoea aquatic. In this study, the CDs derived from the peels of dragon fruit not only acted as nutrients carrier of nitrogen-phosphor-potassium (NPK) fertilizer but also were as supplementation in the enhancement of plant growth.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…This is the first report on employing the unique dual‐emission trait to augment plant photosynthesis. In 2020, this research team prepared far‐red CDs that can convert ultraviolet light into far‐red emission [57] (Figures 7a, 7b) and NaYF 4 :Yb,Er@CDs nanocomposites that can convert NIR irradiation into red light (Figures 7c, 7d) [58] …”
Section: Interaction Between Cds and Plantsmentioning
confidence: 99%